P12.08.A Uncovering the glioblastoma tumor-microenvironment by high-end multiplexing with imaging mass cytometry. (5th September 2022) - Anand, A; Harwood, D S; Bishop, C; Todd, K; Ellis, R; Ellis, R; Poulsen, F R; Kristensen, B W
Abstract: Background: Glioblastoma is one of the most aggressive cancers, and hypoxia plays an essential role in its tumor- microenvironment. Tumor-associated microglia and macrophages (TAMs) have been reported to constitute up to 30 % of the cells, a fraction that is even higher in hypoxic areas. Single-cell mRNA sequencing of glioblastoma tumors has revealed vast heterogeneity, but the spatial aspects are not entirely defined yet. The aim of this study was to uncover differences between the hypoxic and normoxic tumor-microenvironment of human glioblastoma by high-end multiplexing with imaging mass cytometry. Material and Methods: A tissue microarray (TMA) with normoxic and hypoxic areas from 4 IDH-wildtype glioblastomas was prepared based on the hypoxia marker hypoxia-inducing factor 1 alpha (HIF1 alpha). The TMA was stained with 18 metal-tagged antibodies covering TAMs, lymphocytes, immune checkpoints, vessels, tumor cells and proliferation. The Hyperion-CYTOF technology was used to ablate the samples and the images were analyzed by MCD viewer, Visiopharm software, and customized R scripts. Results: Single-cell analysis of 160 fields covering around 45, 000 cells in the glioblastoma microenvironment revealed multiple cellular phenotypes. It was revealed that proliferating TAMs (IBA1+, Ki67+) were more frequent in hypoxia, whereas proliferating vessels (CD34+, Ki67+) were more frequent in normoxia. Additionally, proliferating stem-like tumor cells (OLIG-2+, Ki67+) were more frequent in normoxia regions. Conclusion: Our study revealed multiple cellular phenotypes in the glioblastoma microenvironment. The TAMs, endothelial and tumor cell phenotypes revealed may play a critical role in glioblastoma biology however this needs to be elucidated in future studies.